1985
DOI: 10.1037/0278-6133.4.6.569
|View full text |Cite
|
Sign up to set email alerts
|

Disqualified and qualified poor sleepers: Subjective and objective variables.

Abstract: Sleep laboratory studies of patients complaining of insomnia have demonstrated discrepancies between subjective reports and electroencephalograph (EEG)-recorded measures. In our research studies on sleeping aids, 60% of the self-described poor sleepers who reported usual sleep latencies of at least 45 min did not meet the laboratory qualification criterion of a 30-min or longer sleep latency. To learn to predict who would qualify for our studies, we compared 30 laboratory-qualified poor sleepers (QPSs) with 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…Except for diary reports of less total sleep time, no significant differences in sleep between good sleepers and individuals with insomnia in the full sample were observed. The finding that individuals with insomnia symptoms subjectively reported less total sleep time than good sleepers in their sleep diaries, despite no observable differences in PSG measure of total sleep time, is consistent with the existing literature (e.g., [77][78][79][80]). We identified that eight of the fourteen insomnia participants had a night of poor sleep, while six of the fourteen insomnia participants had a good night of sleep.…”
Section: Sleep and Emotion Processing Group Differencessupporting
confidence: 89%
“…Except for diary reports of less total sleep time, no significant differences in sleep between good sleepers and individuals with insomnia in the full sample were observed. The finding that individuals with insomnia symptoms subjectively reported less total sleep time than good sleepers in their sleep diaries, despite no observable differences in PSG measure of total sleep time, is consistent with the existing literature (e.g., [77][78][79][80]). We identified that eight of the fourteen insomnia participants had a night of poor sleep, while six of the fourteen insomnia participants had a good night of sleep.…”
Section: Sleep and Emotion Processing Group Differencessupporting
confidence: 89%
“…Although self-report studies provide important information on the subjective experience of sleep disturbance, they are typically poorly correlated with objective measures of sleep. 23,24 Past studies of sleep-disordered breathing, on the other hand, used only cardiorespiratory and electroencephalogram measurement in the sleep laboratory setting and provided little information about sleep occurring during daily life. Combining objective sleep measures with subjective indicators may assist in quantifying characteristics of sleep and group-related differences and may also provide a more complete perspective on the nature of sleep disturbance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…measuring movements, EEG, blood pressure or other advanced techniques. On the other hand some researchers have chosen to question the validity of self- reporting [8]. …”
Section: Introductionmentioning
confidence: 99%